Long-term results of cementless humeral head resurfacing for humeral head osteonecrosis - a monocentric longitudinal observational study - Bülhoff, Matthias; Gurda, Amina; Weishorn, Johannes; Spranz, David Maximilian; Knappe, Kevin; Raiss, Patric; Trefzer, Raphael (International orthopaedics, 2025)
Purpose: Humeral head osteonecrosis (HHN) is a joint-destructive condition, for which cementless humeral head resurfacing (CHHR) offers a bone-preserving treatment option. The aim of this study was to report long-term outcomes and implant survival of CHHR in patients with HHN. Methods: Patients with humeral head osteonecrosis treated with cementless humeral head resurfacing (CHHR) between 2004 and 2007 were included. Implant survival was assessed according to Kaplan-Meier analysis. Clinical evaluation included Constant-Murley-Score (CMS), Simple Shoulder Test (SST), Subjective Shoulder Value (SSV) and patient centered outcomes regarding satisfaction and quality of life. Radiographs were evaluated for glenoid erosion, Walch glenoid types as well as signs of implant loosening. Statistical comparison was performed using students t-tests with a significance level set to p < 0.05. Results: Seventeen shoulders were retrospectively included in the implant survival analysis. Two patients underwent revision surgery. five patients died with the implant and were therefore censored. Cumulative survival rate was 100% after ten years and 93.3% after 15 years. Seven shoulders were available for clinical and radiological evaluation at a mean follow-up of 19 years (range 17–22 years). Age- and sex-adjusted CMS improved from preoperative to the latest follow-up (44.4% vs. 82.9%; p < 0.01). No glenoid erosion of higher degree (Sperling grade > 2) and no signs of implant loosening were observed. All patients had Walch type A glenoids preoperatively. Conclusion: In this small cohort with long-term follow-up of 17–22 years, CHHR showed promising durability and functional outcomes in carefully selected patients. Level of evidence: Level IV Case series with no comparison group.
Online veröffentlicht: 18. August 2025
Gesehen am 09.01.2026